Former smokers with non‐small‐cell lung cancers: a comprehensive investigation of clinicopathologic characteristics, oncogenic drivers, and prognosis - Zheng, Shanbo (Cancer Med, 2016)
The aim of this present investigation was to evaluate the clinicopathologic characteristics, oncogenic drivers, and prognosis of former smokers with non‐small‐cell lung cancer (NSCLC), and to compare them with those of the current and never smokers. This investigation was a single‐institution retrospective study of 2289 NSCLC patients, who were classified as former, current, or never smokers. A collection was made of the clinicopathological characteristics, spectra of well‐identified driver genes and survival rates. The survival rates were compared using log‐rank test, and independent prognostic factors, identified using Cox regression analysis. Of 2289 NSCLC patients, 257 (11.2%) were former smokers; 868 (37.9%), current smokers; and 1164 (50.9%), never smokers. Compared with the current, the former were characterized by older age at diagnosis (64.3y vs. 59.9y; P < 0.001), earlier TNM stage (stage I, 47.9% vs. 39.5%; P = 0.017), fewer solid predominance in adenocarcinomas (16.2% vs. 29.5%; P = 0.005), and more EGFR mutation (33.2% vs. 20.7%; P < 0.001) but less KRAS mutation (6.7% vs. 11.9%, P = 0.041). No statistically significant survival differences were observed between the former and current. However, the light former smokers presented favorable overall survival when compared with the light current and heavy former or current (the light former vs. the heavy former, P = 0.028; the light former vs. the light current, P = 0.048; and the light former vs. the heavy current, P = 0.048). Our findings suggest that the former smokers with NSCLCs can have distinctive clinicopathologic characteristics, oncogenic drivers, and prognosis, and they, especially the light former, can benefit from smoking cessation.